MicroRNA-17 is downregulated in esophageal adenocarcinoma cancer stem-like cells and promotes a radioresistant phenotype - Maher, Stephen; Lynam-Lennon, Niamh; Reynolds, John; O'Leary, John; Heavey, Susan; Sommerville, Gary; Bibby, Becky A.S.; Ffrench, Brendan; Quinn, Jennifer; Gasch, Claudia; Gallagher, Michael F. (My University, 2017)
Resistance to neoadjuvant chemoradiation therapy (CRT) remains a critical barrier to the effective treatment of esophageal adenocarcinoma (EAC). Cancer stem-like cells (CSCs) are a distinct subpopulation of cells implicated in the resistance of tumors to anti-cancer therapy. However, their role in the resistance of EAC to CRT is largely unknown. In this study, using a novel in vitro isogenic model of radioresistant EAC, we demonstrate that radioresistant EAC cells have enhanced tumorigenicity in vivo, increased expression of CSC-associated markers and enhanced holoclone forming ability. Further investigation identified a subpopulation of cells that are characterised by high aldehyde dehydrogenase (ALDH) activity, enhanced radioresistance and decreased expression of miR-17-5p. In vitro, miR-17-5p was demonstrated to significantly sensitise radioresistant cells to X-ray radiation and promoted the repression of genes with miR-17-5p binding sites, such as C6orf120. In vivo, miR-17-5p was significantly decreased, whilst C6orf120 was significantly increased, in pre-treatment EAC tumour samples from patients who demonstrated a poor response to neoadjuvant CRT. This study sheds novel insights into the role of CSCs in the resistance of EAC to CRT and highlights miR-17-5p as a potential biomarker of CRT sensitivity and novel therapeutic target in treatment resistant EAC.
PUBLISHED
Keywords: Esophageal Adenocarcinoma; Radioresistance; Cancer stem-like cells; MicroRNA; Biomarker; Cancer